KAJIAN HUKUM PUTUSAN NOMOR: 01/PID.TIPIKOR/2013/PN.TTE TENTANG PENJATUHAN TINDAK PIDANA KORUPSI - Larumpa, Renaldi Markus; Selfianus Laritmas; Usak (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Corruption is a problem that greatly disrupts the state's financial system. So corruption is dubbed as an extraordinary crime (extraordinary crime). Therefore, criminal acts of corruption are specifically regulated in Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Criminal Acts of Corruption. Even though it is specifically regulated, in the judicial process of corruption, judges often give inappropriate sentences. Then in their consideration, the judges often do not pay attention to the principles of criminal law to punish the guilty. In line with that, through the normative research method, the authors use a case approach to analyze the judges' considerations in the decision Number: 01/Pid.Tipikor/2013/PN. Which sentenced the defendant to 7 (seven) years in prison. The verdict is not under the actions of the defendant, because the defendant's actions that were proven were only mistakes (schuld) in the form of negligence (culpa) and not intentionally (dolus). Therefore, the defendant should have been sentenced to less than 7 (seven) years because negligence is a lighter form of error than intentionally (Eddy, 2016: 187). This principle is very important in determining sentencing by judges. So that in terms of imposing a crime, the judge must pay attention to the forms of errors that can alleviate and burden both from the perspective of the defendant and the community by referring to the sentencing guidelines, so that these decisions are in line with the objectives of criminal law.